Progeria - the old children - Dawid Dziedziński; Dawid Łoś; Aleksandra Nowak; Anita Janus; Agata Kaptur (Nicolaus Copernicus University in Toruń, 2024)
Introduction and Purpose: Progeria, also known as Hutchinson-Gilford progeria syndrome, is a rare genetic disorder characterized by accelerated aging in children. This research article aims to provide a comprehensive overview of progeria, including its etiology, symptoms, diagnosis, and treatment options. By synthesizing existing knowledge, this study seeks to enhance understanding and promote effective management strategies for individuals affected by this condition.   Description of the State of Knowledge: Progeria is an exceedingly rare genetic disorder, with an estimated incidence of approximately one in every 4 to 8 million births worldwide. It manifests early in childhood, leading to premature aging and a spectrum of associated health complications. The condition is primarily caused by a mutation in the LMNA gene, resulting in the production of a defective form of the protein lamin A. This abnormal protein disrupts the structural integrity of the cell nucleus, contributing to the characteristic features of progeria. Despite advances in medical research, there is currently no cure for progeria, and treatment options focus on managing symptoms and improving quality of life.   Summary: This research article provides a comprehensive overview of progeria, highlighting its genetic basis, clinical manifestations, diagnostic criteria, and therapeutic interventions. By elucidating the state of knowledge surrounding progeria, this study aims to facilitate early detection, enhance medical care, and foster ongoing research efforts aimed at advancing treatment modalities for affected individuals.